Submanifolds with the Harmonic Gauss Map in Lie Groups - Petrov, Ye. V. (Журнал математичної фізики, аналізу, геометрії, 2008)
In this paper we find a criterion for the Gauss map of an immersed smooth submanifold in some Lie group with left invariant metric to be harmonic. Using the obtained expression we prove some necessary and sufficient conditions for the harmonicity of this map in the case of totally geodesic submanifolds in Lie groups admitting biinvariant metrics. We show that, depending on the structure of the tangent space of a submanifold, the Gauss map can be harmonic in all biinvariant metrics or nonharmonic in some metric. For 2-step nilpotent groups we prove that the Gauss map of a geodesic is harmonic if and only if it is constant. Mathematics Subject Classification: 53C42, 53C43, 22E25, 22E46.